Answer:
-3
Step-by-step explanation:
-5 1/2 + 6 3/4 - 4 1/4
= 1 1/4 - 4 1/4
= -3
9514 1404 393
Answer:
top-down
f(g(x)) = 1, 4, 5, 3, 2
g(f(x)) = 5, 2, 4, 1, 3
Step-by-step explanation:
To find f(g(x)), locate g(x) in the third column (labeled g(x)). Use that value as x in the first column, then read f(x) from the second column.
Example: f(g(1)) = f(2) = 1
__
To find g(f(x)), locate f(x) in the second column (labeled f(x)). Use that value as x in the first column, and read the corresponding g(x) from the third column.
Example: g(f(1)) = g(2) = 5
The answer for the exercise shown above is the first option, which is:
<span> f(x)=log(x-3)
The explanation is shown below:
If you substitute the x in the function for values, you will obtain the graph attached above. As you can see on the mentioned graph, when the variable x has the value 4, the value y is 0. Therefore, you have:
</span> f(x)=log(x-3)
f(x)=log(4-3)
f(x)=log(1)
f(x)=0<span>
</span>
Answer:
Plug in your variables value.
Step-by-step explanation:
For your case, plug in -6 into the y slot
12(5+2y)= -(6-9y) +4y
12(5+2x-6)= -(6-9x-6)+4y see if that works!